Promise of autologous CD34+ stem/progenitor cell therapy for treatment of cardiovascular disease. Issue 8 (5th February 2020) - Prasad, Megha; Corban, Michel T; Henry, Timothy D; Dietz, Allan B; Lerman, Lilach O; Lerman, Amir
Abstract: CD34+ cells are haematopoietic stem cells used therapeutically in patients undergoing radiation or chemotherapy due to their regenerative potential and ability to restore the haematopoietic system. In animal models, CD34+ cells have been associated with therapeutic angiogenesis in response to ischaemia. Several trials have shown the potential safety and efficacy of CD34+ cell delivery in various cardiovascular diseases. Moreover, Phase III trials have now begun to explore the potential role of CD34+ cells in treatment of both myocardial and peripheral ischaemia. CD34+ cells have been shown to be safe and well-tolerated in the acute myocardial infarction (AMI), heart failure, and angina models. Several studies have suggested potential benefit of CD34+ cell therapy in patients with coronary microvascular disease as well. In this review, we will discuss the therapeutic potential of CD34+ cells, and describe the pertinent trials that have used autologous CD34+ cells in no-options refractory angina, AMI, and heart failure. Lastly, we will review the potential utility of autologous CD34+ cells in coronary endothelial and microvascular dysfunction.